Servikal spondilotik myelopatilerde anterior cerrahi teknikler - HARMAN, FERHAT (My University, 2022)
Servikal spondilotik miyelopati, 55 yaş üstü hastalarda en sık görülen dejeneratif omurga problemidir. İlerleyici spinal kanalda daralma olması durumunda omurilikte direkt bası etkisi haricinde iskemik hadiseler neticesinde miyelomalazi gelişebilmektedir. Bu olguların erken tanı ve tedavisinde ilerleme kaydedilmesine rağmen cerrahi tedavisinde optimal yaklaşımla ilgili tartışmalar devam etmektedir. Servikal dar kanal cerrahisinde anterior servikal diskektominin, korpus hizasında dekompresyon sınırlarının kısıtlılığı nedeniyle endikasyonları sınırlıdır. İki seviye üzerinde korpektomi yapılması füzyon ve enstrümantasyon başarısızlıklarını artırabilmektedir. Bunu önleyebilmek adına atlayarak korpektomi tekniği önerilmiştir. Atlayarak korpektomi, arada bir korpus korunduğu için daha kısa greftler ve enstrümantasyon kullanımına izin verir. Böylece sıyırma kuvvetlerinin azaltılması hedeflenir. Oblik korpektomi enstrümantasyon kullanılmaması avantajına sahiptir ancak cerrahi oryantasyon kaybı yaşanabilmektedir. Bu yazımızda servikal spondilotik miyelopati hastalarında anterior yaklaşımla uygulanan cerrahi tedaviler ele alınmıştır.

Cervical spondylotic myelopathy is the most common degenerative spine problem in patients over 55 years of age. In case of progressive narrowing of the spinal canal, myelomalacia may develop as a result of ischemic events in addition to the direct compressive effect on the spinal cord. Although progress has been made in the early diagnosis and treatment of these cases, discussions about the optimal approach in the surgical treatment continue. Anterior cervical discectomy has a limited number of indications due to the restrictions in the decompression limits at the corpus level. In addition, the possibility of developing complications has been found to be higher with multi-level corpectomy. More than two levels of corpectomy may increase fusion and instrumentation failures. In order to prevent this, the skip corpectomy technique has been suggested. Skip corpectomy allows the use of shorter grafts and instrumentation as some corpi are preserved with skipping, aiming to reduce the stripping forces. Oblique corpectomy has the advantage of not using instrumentation, but loss of surgical orientation can occur. In this article, the surgical treatments applied with the anterior approach in patients with cervical spondylotic myelopathy are discussed.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Anterior yaklaşım; Korpektomi; Servikal spondilotik miyelopati; Servikal diskektomi; Servikal dar kanal; Anterior approach; Corpectomy; Cervical spondylotic myelopathy; Cervical discectomy; Cervical spinal stenosis